Ефективність упровадження методики вдосконалення техніко-тактичної підготовки дітей 15–16 років у процесі занять спортивним туризмом у річному циклі тренувань - Дем’янчук, Олена Григорівна; Demyanchuk, Olena (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті здійснено аналіз та застосовано метод узагальнення науково-дослідної й науково-методичної літератури, висвітлено погляди фахівців на основи теорії тренувань та побудову процесу підготовки спортсменів, які займаються спортивним туризмом. Завданням нашого дослідження – доказати ефективність застосування розробленої нами методики вдосконалення техніко-тактичної підготовки дітей 15–16 років у тренувальному процесі річного циклу. The article deals with the analysis and application of the method of generalization of research and scientific-methodological literature. It was also highlighted the experts’ views concerning the basics of training theory and formation of the process of athletes’ preparation who practice sports tourism. The task of our research was to prove the efficiency of application of the developed by us methodology of improvement of technical-tactical preparation of children aged 15–16 years old for the training process of an annual cycle.
The Effectiveness of Implementation of the Methodology of Improvement of Technical and Tactical Training of Children aged 15–16 Years old in the Process of Sports Tourism Practicing in an Annual Training Cycle
Keywords: спортивний туризм; методика вдосконалення техніко-тактичної підготовки; sports tourism; methodology of improvement of technical and tactical preparation